Pemanfaatan Media Pembelajaran Geografi di SMA/MA Nahdatul Wathan Kabupaten Lombok Timur - Putra, Agus Muliadi; Suroso, Suroso (Educatio, 2017)
This study aims to find out 1). Availability of learning media 2). Utilization 3). Difficulties faced by teachers, 4). Efforts made by geography teachers to be able to utilize geography learning media at SMA / MA Nahdatul Wathan East Lombok Regency. This type of research is quantitative descriptive. The population in this study were all geography teachers who taught class XII IPS and all students of class XII IPS in SMA / MA Nahdatul Wathan in East Lombok Regency. Data retrieval is done by using questionnaire method, interview and observation. The results of the study show that 1) The availability of media includes: a) the most types of media are globe and map b) the number of media is classified as poor and c) the condition of the media is considered good. 2) The use of media is seen from: variations in media classified as moderate (73.33 percent); the driving factor for choosing the media is high (73.33 percent); student responses are high (60 percent) and student opportunities are high (53.33 percent). 3) Teacher difficulties are high (80 percent). 4) Teacher efforts are classified as moderate (80 percent)